PEMBARUAN ISLAM BIDANG KELUARGA: RELEVANSI DAN SOLUSI TERHADAP PERSOALAN NUSYUZ: Indonesia - Hulaimi Azhari (Universitas Islam Negeri Mataram, 2021)
Before the arrival of Islam, Arab society was a society that was far from orderly and according to norms. Customs, morals, and life rules adopted are habits that have existed for a long time and are adopted as habits and beliefs. In a society that is oriented towards human values, Islam comes with a concept that forms the order of pre-Islamic Arab society in a relatively precise manner. Islam as a religion changes several aspects of society, one of which is in the family. One of the discussions in the family field is the remaining settlement of nusyuz in Islam where nusyuz is a disobedient attitude between husband and wife. This type of writing is a literature study, namely a study in which data collection is obtained from various scientific literacy such as books, journals, articles, and others. The data of this study consisted of secondary and primary data with qualitative methods. The findings resulted that the offer of another Qur'an was first, offering advice to the wife in a ma'ruf or good way which aims to awaken the wife from her wrong actions. Second, as a psychological punishment for the wife and in her solitude for committing a crime against her punishment. Third, giving physical punishment to the wife.